A screen of small molecule and genetic modulators of life span in female Drosophila identifies etomoxir, RH5849 and unanticipated temperature effects. Issue 1 (31st December 2022) - N. Landis, Gary; Ko, Sebastian; Peng, Oscar; Bognar, Brett; Khmelkov, Michael; S. Bell, Hans; Tower, John
ABSTRACT: Mifepristone increases life span in female Drosophila melanogaster, and its molecular target(s) remain unclear. Here small molecule and genetic interventions were tested for ability to mimic mifepristone, or to decrease life span in a way that can be rescued by mifepristone. Etomoxir inhibits lipid metabolism, and significantly increased life span in virgin and mated females, but not males, at 50 µM concentration. Pioglitazone is reported to activate both mammalian PPARγ and its Drosophila homolog Eip75B. Pioglitazone produced minor and inconsistent benefits for female Drosophila life span, and only at the lowest concentrations tested. Ecdysone is a Drosophila steroid hormone reported to regulate responses to mating, and RH5849 is a potent mimic of ecdysone. RH5849 reduced virgin female life span, and this was partly rescued by mifepristone. Mifepristone did not compete with RH5849 for activation of an ecdysone receptor (EcR)-responsive transgenic reporter, indicating that the relevant target for mifepristone is not EcR. The conditional GAL4/GAL80ts system was used in attempt to test the effect of an Eip75B RNAi construct on female life span. However, the 29°C temperature used for induction reduced or eliminated mating-induced midgut hypertrophy, the negative life span effects of mating, and the positive life span effects of mifepristone. Even when applied after mating was complete, a shift to 29°C temperature reduced mating-induced midgut hypertrophy by half, and the life span effects of mating by 4.8-fold. Taken together, these results identify promising small molecules for further analysis, and inform the design of experiments involving the GAL4/GAL80ts system.